Ring Chromosome 4 in a Child with Multiple Congenital Abnormalities: A Case Report and Review of the Literature - C. S. Paththinige; N. D. Sirisena; U. G. I. U. Kariyawasam; L. P. C. Saman Kumara; V. H. W. Dissanayake (Case Reports in Genetics)
A female child born preterm with intrauterine growth retardation and presenting with facial dysmorphism with clefts, microcephaly, limb deformities, and congenital abnormalities involving cardiovascular and urinary systems is described. Chromosomal analysis showed a de novo 46,XX,r(4)(p15.3q35) karyotype. The clinical features of the patient were compared with the phenotypic characteristics of 17 previously reported cases with ring chromosome 4 and those with Wolf-Hirschhorn syndrome (4p-). Clinical features observed in this case are consistent with the consensus phenotype in ring chromosome 4. Patent ductus arteriosus and bilateral talipes equinovarus observed in this baby widen the phenotypic spectrum associated with ring chromosome 4.